Camaraderie, Culture, and Connection: A Photovoice of a Long-Term International Fellowship - Jessica R. Spence; Meikah Dado (Journal of International Agricultural and Extension Education, 2025)
As globalization intensifies, the demand for culturally competent professionals rises, necessitating innovative approaches to international education. This study delves into the transformative learning experiences of participants engaged in long-term agricultural education fellowships in Ghana. The research involved a cohort of nine agriculture graduates participating in a program aimed at agricultural education and food security initiatives in rural Ghana. Through the innovative method of photovoice, participants visually documented and reflected on their experiences, generating rich data for analysis. The findings revealed ten prominent themes encompassing the fellows' initial month abroad, including Camaraderie, Struggles, Recognition of Empowered Women, Appreciation of Culture and History, Exploration, Finding Community, Personal Growth, Time in School & 4-H Ghana, Student Appreciation & Connection, and Agriculture Knowledge Gain and Appreciation. This study provides valuable insights into the transformative potential of long-term agricultural education fellowships, shedding light on participants' intricate interplay with the local community, culture, and educational system. Recommendations for program enhancements, including tailored training on cultural acclimation, gender-specific empowerment, and increased emphasis on historical and cultural site training, are offered to maximize the impact and effectiveness of similar initiatives in the future.
Keywords: Ghana; Sub Saharan Africa; International development; Agriculture Education; Transformational learning